The Impact of Human Behavior on the Unnatural Evolution of Animals - You, Canfei (Transactions on Environment, Energy and Earth Sciences, 2024)
For millions of years, natural selection has shaped the evolution of species, with environmental factors determining their survival and reproductive success. However, in recent centuries, human activities have introduced a new force—artificial evolution—driven by behaviors such as feeding, poaching, and habitat destruction. This review explores how these human interactions have reshaped the evolutionary trajectories of various species. One case study on fallow deer in Phoenix Park demonstrates how human feeding behaviors increased reproductive success by boosting fawn body mass, giving them a survival advantage. Additionally, the review examines how poaching has led to the decline of desirable traits, such as tusk size in elephants, due to the selective removal of individuals with larger tusks. The findings suggest that human actions are significantly influencing natural selection, with both intentional and unintentional effects. Understanding these impacts is crucial for addressing the long-term consequences of human-driven evolution and ensuring the preservation of biodiversity and ecosystem stability.